Japan - Davis, F. Hadland (T. C. & E. C. Jack, limited, 1916)
Contents: The Ainu, and the coming of the Japanese; The age of the Gods; From Jimmu to Jingo; From Ojin to Senkwa; The coming of buddhism; The Fujiwara and the Nara period; Kiyomori and the Taira; Two famous warriors; The wars of the Gem-pet...